From megaproject to white elephant lessons from the Philippines's Bataan nuclear power plant - Mendoza, Ronald U.; Bertulfo, Donald Jay; Cruz, Jerome Patrick D. (Philippine studies : historical and ethnographic viewpoints, 2018)
"Drawing from recent literature on white elephant projects, this article examines the case of the Bataan Nuclear Power Plant (BNPP)-the paradigmatic example of a white elephant project in the Philippines. The BNPP megaproject had massive implications for the country's fiscal standing and long-term economic prospects, offering lessons for future projects of this size and significance. By revisiting the BNPP's problematic history as well as the continuing infrastructure governance challenges in the post-Marcos period, this study outlines the repercussions of such dynamics for the Philippine government's "Build, Build, Build" infrastructure program, the most ambitious since the Marcos era."